Nosocomial infection in intensive care unit: a retrospective analysis - Jamhuri, Jamaidah Jamorek (2010)
Intensive-care-unit (ICU)-acquired infection rates are 5-10 times higher than hospital acquired infection rates in general ward patients. Knowledge in the use of antibiotics in ICU is important to ensure an optimal clinical outcome, and also control the emergence of resistance among pathogenic microorganisms as well as to reduce cost. The aim of this retrospective study was to detennine the current status of ICU infection in Hospital Universiti Sains Malaysia. (HUSM) A retrospective review of nosocomial infection in HUSM over one year period from April 2008 to March 2009 was perfonned. Nosocomial infections (Nls) were defined according to the Centers for Disease and Prevention. The overall patient Nls rate, the incidence density rate of Nls, patients' demography, length of ICU stays, days on devices, type of nosocomial infection, the Simplified Acute Physiology Score (SAPS) II score and outcome were determined. The organisms and antimicrobial susceptibility profiles were further investigated. From 795 patients admitted to ICU, 60 patients were identified with nosocomial infections. The overall Nls rate was 7.5 per 1 00 patients, with incidence density rate 91 per 1000 days .The mean length of stays was 17.13 ± 10.11 days. Patients with diabetes mellitus and hypertension were almost similar to patients with no co-morbidities (33.3%; 36.7% versus 31.7%). The mean SAPS II score w~s 41.82 ± 16.5. Outcome of patients who survived was 56.7%, whereas 6.7% was readmitted to ICU. The main type of Nls were bacteremia and pneumonia (38.3%) with gram negative bacteria as the main organism isolated (59.6%). The main organism isolated was Acinetobacter sp. (24.5%) from tracheal aspirate. The initial therapy was monotherapy mainly by meropenem (29.8%) and the least used was cephalosporins. Four main organisms developed resistant were Acinetobacter sp. (28.6%), Klebsiella sp. (14.3%), MRSA (14.3%) and E. coli (7.1 %).There were no specific resistant to any group of antibiotics. Five cases of multidrug-resistant Acinetobacter sp. were isolated (35.7%), whereby three cases of extended-spectrum beta lactamases (ESBLs) Klebsiella sp. and E. coli were isolated (21.4%). Gram negative organism remain the main pathogen in ICU infection with the main pathogen was Acinetobacter sp. that potentially could lead to the emergence of multidrug-resistant. A future local prospective study would facilitate the surveillance ofiCU infection.